2015
DOI: 10.1016/j.jnci.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of laparoscopic colo-rectal surgery for cancer at a tertiary center in a developing country: Egypt as an example

Abstract: Laparoscopic colorectal surgery for cancer in developing countries could be safe and feasible. Safe reuse of disposable expensive parts of some laparoscopic instruments could help in propagation of this technique in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…In a previous study, we showed that laparoscopic colorectal surgery for malignant tumors in developing countries is potentially feasible and safe, and gave similar results for that of multicenter trials [22].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In a previous study, we showed that laparoscopic colorectal surgery for malignant tumors in developing countries is potentially feasible and safe, and gave similar results for that of multicenter trials [22].…”
Section: Discussionsupporting
confidence: 59%
“…Evidences for the possibility to sterilize the single use devices even with the contamination-challenge are present [25]. For economic issues we safely re-used vessel sealing bipolar devices several times which could be cost-effective [22] [26] [27]. The cost has been reduced by about 70% that means 500 US Dollars at the time of the study which is a good financial benefit regarding Egypt economy.…”
Section: Discussionmentioning
confidence: 99%
“…There are similar lags in laparoscopic surgery in many developing countries in Latin America, Asia, and Sub-Saharan Africa 812. The importance of these data is put into context when we consider that the cumulative population of the developing world iŝ2 billion persons 13…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, because of limited resources and the expenses of MIS, laparoscopic colorectal surgery is restricted in use for a few tertiary centers with only few cases being treated every year. However, studies from Egypt have showed that various types of laparoscopic colo-rectal surgery for cancer with the adoption of the standardized operative steps respecting the oncologic fundamentals could be performed successfully without jeopardizing oncologic safety [11] .…”
Section: Introductionmentioning
confidence: 99%